2018
DOI: 10.1111/jre.12610
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease susceptible matrilines in the Cayo Santiago Macaca mulatta macaques

Abstract: Objective and Background: The expression of periodontitis, including age of onset, extent, and severity is considered to represent an interaction of the individual's oral microbiome and host response to the microbial challenge that is modified by both genetics and environmental factors. The aim of this study was to determine the distribution of periodontitis in a population of nonhuman primates, to document features of familial distribution that could reflect heritability and transmission of microbes with enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 57 publications
3
23
0
1
Order By: Relevance
“…We have also recently reported a familial relationship of periodontitis susceptibility and resistance in multigenerational matrilines of Macaca mulatta 14 consistent with some heritability/genetic contribution to the disease, as has been described in humans [17][18][19] .…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…We have also recently reported a familial relationship of periodontitis susceptibility and resistance in multigenerational matrilines of Macaca mulatta 14 consistent with some heritability/genetic contribution to the disease, as has been described in humans [17][18][19] .…”
Section: Introductionsupporting
confidence: 64%
“…Thus, we and others have employed a nonhuman primate model of periodontal disease over the last nearly 40 years. It has been shown that the microbiology, immunology, and clinical expression of periodontitis are quite similar in humans and nonhuman primates, including naturally-occurring disease that increases with aging [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, epidemiologic data support various demographic modifiers (e.g., age, sex) of periodontitis expression in humans, as well as the identification of substantial individual variation in risk for more extensive and severe disease. While the ligature model does not necessarily reflect this individual feature of human periodontitis, we have shown that the magnitude of ligature‐induced disease in the nonhuman primates is altered by age 56 and sex, 111 as well as recent data demonstrating matriline (e.g., genetic, familial) susceptibility age of onset and extent of disease 112,113 . Thus, the evidence suggests that this model should be able to provide some insights into the earliest phases of disease initiation and progression that would be difficult to obtain in a human disease model.…”
Section: Discussionmentioning
confidence: 80%
“…Sven Mario Anaya Espinoza más parecidas a las de los humanos se encuentran en los monos Rhesus. Por lo tanto, se recomienda que los futuros estudios se lleven a cabo en monos de esa especie ( [36][37][38][39][40][41][42] ).…”
Section: Estabilidad Y Porcentajes De Recidiva De La Técnica Fcs a Launclassified